Reading the Signs”: Aspects of Perception of a Game Polycode Text in Space of a Modern City - T. A. Gridina; N. I. Konovalova (Научный диалог)
One of the new linguocreative practices of organizing the city space as a cultural text is analyzed. The game discourse of polycode texts is considered, which combine elements of different semiotic systems: signs of traffic rules, supplemented by visualized symbolic allusions and quotations, collectively referring to the motifs of famous works of art. The constructive principles of modeling the associative context of polycode posters placed in the Literary Quarter of Yekaterinburg are characterized. The universality of the generation of game texts of any semiotic nature on the basis of an operational technique that creates the effects of associative deducibility and associative integration is substantiated. The novelty of the study is related to the description of the algorithm for creating and deciphering a game polycode text of this type, identifying the factors and strategies for reading it by the addressee. The dynamic component of the semantic diversity of the analyzed texts is experimentally verified, taking into account the respondents’ recognition of the prototypes of the game transform, reflection on the connection between its visual and verbal components, and the ability to derive allusive implicatures. Particular attention is paid to the analysis of game transform decoding strategies in the light of the mechanisms of linguocreative thinking based on the switching of associative stereotypes in the language game register.